THE IMPLEMENTATION OF PORTOFOLIO – BASED ON LEARNING TO INCREASE STUDENTS’ RESPONSIBILITY AND ACHIEVEMENTS (Study On Indonesia Lesson on Students of XI Grade at SMA Negeri 1 Lebong District) - Dedi Supriadi; Nina Kurniah (UNIB Press, 2019)
This research was aimed to describe the increasing of students’ responsibilities and achievements, and to increase learning activities throught the implementation of portofolio – Based on learning study on Indonesia lesson on students of XI ade at SMA Negeri 1 Lebong District. The method used was classroom Action Research (CAR) that guided by quasi experiment. The subjects of this research was on XI IPA 3 Grade students as a Classroom Action Research (CAR) and XI IPA 4 as an experiment Classroom. Whereas, XI IPA 1 was a Classroom Control. The instrument used was the teacher’s abservation activities sheet, the students’ observation of responsibilities sheet, and t – test sheet. The result of this research showed that the implementation of portofolio- Based on Learning is able to increase the students’ responsibilities and achievements as well as affectivity applied on XI Grade Students at SMA Negeri 1 Lebong District